Understanding the Motifs and Symbolism in the East Asian Porcelain from the Collection of the National Museum of Slovenia - Berdajs, Tina (Poligrafi, 2022)
The paper presents an analysis of selected motifs which appear in various examples of decorated porcelain from East Asia which is stored in the ceramics collection of the National Museum of Slovenia. Through an analysis of primary sources and secondary literature, as well as through direct handling of the objects, this paper presents the first overview of decorative styles and selected plant and animal motifs most often encountered on porcelain dated to the period between the first half of the 17th century and the end of the 19th century (or the beginning of the 20th century). Relating to the analysis of motifs and symbolism, three case studies of individual objects are presented, the decorative elements of which give an insight into the rich stories connected with the cultural-historical background of trade and cultural exchanges between Europe and East Asia. The paper highlights examples of Chinese and Japanese export porcelain, which were mass-produced products for Western markets, but decorated with East Asian motifs. The paper leads to a reflection on the role of the studied symbolism in the Japanese and Chinese cultural-historical environments as well as the (potential) role of these motifs in the environment where these objects of East Asian origin eventually came to be, i.e., in the area of today’s Slovenia.